A Study on the Linking the Supply Chain Management to Value of Manufacturing Companies Listed in Indonesia Stock Exchange - Rina Maria Hendriyani; Disman Disman; Nugraha Nugraha; M. Wahyudin Zarkasyi (International Journal of Supply Chain Management, 2020)
Abstract-With the advancement of information and communication technologies, supply chain integration has been considered a strategic tool for firms to improve their competitiveness. The supply chain integration within processes and between organizations has enhanced value creation. The purpose of this study was to determine the effect of profitability ratios, capital structure, exchange rates, interest rates, inflation on the value of manufacturing companies listed on the Indonesia stock exchange in 2008-2017 based on the supply chain management. The analysis technique used multiple regression analysis of panel data. The results showed that profitability ratios, capital structure, exchange rates, interest rates, inflation affect the value of manufacturing companies. The findings are that inflation is the most determining variable in influencing the value of manufacturing companies. The value of manufacturing companies in Indonesia is still influenced by factors such as profitability ratios, capital structure, supply chain strategy and macroeconomics.